STUDI EKSPERIMENTAL PROSES PIROLISIS LIMBAH SISA PRODUKSI SANDAL DITINJAU TERHADAP TEMPERATUR DAN WAKTU - Agung S, Pramoda; Solichin, Mohammad (MEKANIKA: Jurnal Teknik Mesin, 2015)
Pyrolysis is defined as the process of thermal degradation of the solid by heating process in conditions oflittle or no oxygen, or other reagents that allow some conversion paths thermokimia so that these solids into gas(permanent gasses), liquid (pyrolitic liquid) and solids (char)In this experiment we used slippers waste as raw material. LPG gas stove as a heater in a system retort.denganpirollisis temperature variations of 150 ° C, 300 ° C, 350 ° C and 400 ° C with a variation of pyrolysis time of 60min, 90 min and 120 min. With the aim to produce a yield of carbon in the form of charcoal.The experimental results showed that the waste can be processed into a carbon sandals charcoal by pyrolysis.Carbon yield of charcoal produced from this experiment between 36% to 48% with an average yield of 41.425% Keywords: pyrolysis, the waste slippers, carbon charcoal.